2019
DOI: 10.1029/2018jd029848
|View full text |Cite
|
Sign up to set email alerts
|

Surface Meteorological Conditions and Boundary Layer Height Variations During an Air Pollution Episode in Nanjing, China

Abstract: The evolution of planetary boundary layer (PBL) was investigated using observations from a laser ceilometer, an eddy covariance system, and an automatic meteorological station in the north of Nanjing city during an air pollution episode in 2016–2017 winter. Based on 7‐day observation under clean to polluted day, we recorded the temporal variations of backscatter signals observed by the ceilometer, and then intercompared the planetary boundary layer height (PBLH) retrieved from individual methods. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 66 publications
(89 reference statements)
1
10
0
Order By: Relevance
“…Surface forcing response, drag, turbulence, and vertical mixing are strongly evident here and play a critical role within PBL compared to their importance in the overlying “free atmosphere” (Stull, 1988). The PBLH is a vital parameter in climate models, weather forecasts, and air quality prediction (Allabakash & Lim, 2020; Yin et al., 2019). PBLH data are available from the NASA Goddard Earth Sciences Data and Information Services Center (GES DISC), which provides data processing, archiving, and distribution services for many Earth science products.…”
Section: Introductionmentioning
confidence: 99%
“…Surface forcing response, drag, turbulence, and vertical mixing are strongly evident here and play a critical role within PBL compared to their importance in the overlying “free atmosphere” (Stull, 1988). The PBLH is a vital parameter in climate models, weather forecasts, and air quality prediction (Allabakash & Lim, 2020; Yin et al., 2019). PBLH data are available from the NASA Goddard Earth Sciences Data and Information Services Center (GES DISC), which provides data processing, archiving, and distribution services for many Earth science products.…”
Section: Introductionmentioning
confidence: 99%
“…Using the WRF-CMAQ model, Nguyen et al (2019) also found that the ADE could reduce the annual average PBLH in East Asia by -46.47 m (−8.13%). The lower boundary layer caused by aerosols is usually also accompanied by calm winds and higher relative humidity values (Yin et al, 2019). Here, the 10-m wind is found to be slower by -1% to -7.5% (Fig.…”
Section: Aerosol Effect On Meteorologymentioning
confidence: 65%
“…Previous studies have shown that the climatology of the PBLH has significant geographical and seasonal variances ( Seidel et al, 2012;Guo et al, 2016;Zhang et al, 2020a), which is important in research related to climate and air pollution (van der Kamp and McKendry, 2010;Yin et al, 2019). To investigate the spatial variations of the key diurnal features of the PBLH over the CONUS and to facilitate comparisons between our work and previous studies, Figure 2 shows the spatial patterns of the mean PBLH at 0000 UTC and the mean diurnal maximum PBLH in different seasons during the time period 2007-2016.…”
Section: Statistical Analysis Of Pblhsmentioning
confidence: 99%